Getting started with Hazelcast : get acquainted with the highly scalable data grid, Hazelcast, and learn how to bring its powerful in-memory features into your application - Johns, Mat (Community experience distilled., 2015)
This book is a great introduction for Java developers, software architects, or DevOps looking to enable scalable and agile data within their applications. Providing in-memory object storage, cluster-wide state and messaging, or even scalable task execution, Hazelcast helps solve a number of issues that have troubled technologists for years.